Effect of addition of intrathecal midazolam to 0.5% hyperbaric bupivacaine to prolong the post-operative analgesia in lower abdominal surgeries - Adil Hasan, S. K. (International Journal of Advances in Medicine, 2019)
Background: Bupivacaine when used alone produces analgesia for 2.5 to 3 hours, making it unsuitable in cases where the duration of surgery is longer and in cases which require further analgesia during post-operative period. Present study is intended to evaluate the effect of addition of intrathecal midazolam to bupivacaine to prolong the post-operative analgesia. Methods: Present clinical study was conducted in Kamineni Institute of Medical Sciences, Narketpally, Nalgonda District, Andhra Pradesh, India. After obtaining approval from institutional ethical committee, present clinical study was undertaken to evaluate the effects of addition of intrathecal midazolam to bupivacaine 0.5% (heavy). The study was conducted on 60 patients undergoing lower abdominal surgeries. Results: Mean onset of analgesia was 190.5 with SD 21.3 in group-C whereas in group-M, mean onset of analgesia was 185.3 with SD 26.81. Mean difference between the groups not showing statistical significance. In the present study the Maximum height of sensory blockade in control and midazolam group was T7 (T6-T8) compared to T7 (T6-T8) midazolam group. Mean duration of sensory blockade was 130.4 with SD 36.36 in group-C whereas in group-M, mean duration of sensory blockade was 191.9 with SD 36.4. Mean difference between the groups showing statistical significance. Mean duration of motor blockade was 176.3 with SD 23.7 in group-C whereas in group-M, mean duration of motor blockade was 208.1 with SD 18.21. Mean difference between the groups showing statistical significance. Conclusions: Midazolam is a useful adjuvant to bupivacaine in subarachnoid block. Intrathecal midazolam combined with intrathecal bupivacaine produces a longer and more effective anaesthesia and analgesia. It also prolongs post-operative analgesia without increasing adverse effects.